Coking inhibitors, processes for their preparation and use
Patent Information
- Application Number
- CN202610831258.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-27
AI Technical Summary
(1)结焦的热阻是金属受热面热阻的数百倍(约为400倍),导致受热面传热能力急剧恶化,降低炉窑热效率,增加燃料消耗
1.首次将碱性物、稀土氧化物、成核剂、氧化剂、助熔剂和分散剂六类功能组分进行系统复配,各组分在炉窑高温区通过中和、催化、晶化、氧化、助熔、成孔及防腐的链式协同作用,同时实现抑制新焦生成、清除已有结焦、脱硫固硫、助燃节能及受热面防腐保护五大功能。
Abstract
Description
Technical Field
[0001] This invention relates to a coking inhibitor, its preparation method, and its application, belonging to the field of industrial additives. Background Technology
[0002] Various high-temperature furnaces and kilns, such as side-blown furnaces, smelting furnaces, converters, coal-fired boilers, and incinerators, are widely used in industries such as metallurgy, power, and chemicals. During production and operation, due to the complex composition of raw materials, uneven distribution of combustion temperature, and high sulfur and ash content in the fuel, these devices are prone to coking and ash accumulation on heated surfaces (such as water-cooled walls, superheaters, and flue walls).
[0003] The main mechanisms of coking formation include: (1) Low-temperature wet coking: The flue gas produced after fuel combustion contains a small amount of moisture, sulfur trioxide and ash. On the heating surface at a lower temperature, water vapor combines with sulfur trioxide to form sulfuric acid. The sulfuric acid adheres to the surface of the heating surface and continuously captures fly ash in the flue gas. At the same time, it reacts with metal to form sulfate, gradually forming a dense and sticky coking layer.
[0004] (2) High-temperature dry coking: On the heated surface or furnace wall at a high temperature, alkali metals (such as sodium and potassium) in the raw materials react with sulfur and oxygen to generate low-melting-point sulfates (such as Na2SO4 and K2SO4) or eutectic. These low-melting-point substances are in a molten or semi-molten state at high temperature, and are very easy to adhere to the heated surface and continuously thicken to form hard high-temperature coking.
[0005] The damage caused by coking is very serious: (1) The thermal resistance of coking is hundreds of times (about 400 times) that of the metal heating surface, which leads to a sharp deterioration in the heat transfer capacity of the heating surface, reduces the thermal efficiency of the furnace and increases fuel consumption.
[0006] (2) Coking blocks the flue gas passage, increases the resistance to exhaust, forces the equipment to operate at a reduced load, and affects smelting efficiency or steam production.
[0007] (3) Local high temperature or corrosive atmosphere is easily formed under the coking layer. In particular, sulfates and sulfides will accelerate the corrosion of metals and shorten the service life of equipment.
[0008] (4) To remove coking, it is often necessary to stop the machine and clean manually, which is labor-intensive, poses a high safety hazard, and causes production interruption.
[0009] To alleviate the problem of coking, the industry has developed a variety of coking inhibitors or decoking agents. Existing coking inhibitors can be mainly classified into the following categories: (1) Sodium carbonate, calcium hydroxide, etc., rely on neutralizing acidic substances to inhibit coking. However, single-component alkaline substances have a limited effect and cannot effectively break up the hard coking that has already formed. Moreover, if the amount added is too large, it will easily cause the accumulation of alkali metals in the furnace, which will aggravate high-temperature coking.
[0010] (2) Some rare earth oxides (such as cerium oxide) have the function of catalytic combustion and changing the melting point of ash slag, but the cost of using rare earth oxides alone is high, and their ability to remove the coking layer is limited, making it difficult to achieve self-peeling.
[0011] (3) For example, nitrates utilize the active oxygen released by their decomposition to aid combustion and impact ash, but lack the ability to regulate the crystal structure of ash, resulting in unstable decoking effect and inability to form long-term anti-corrosion protection.
[0012] (4) A few patents or commercially available products attempt to simply mix alkaline substances, oxidants, etc., but the components lack synergistic design and are often only targeted at a certain type of coking (low temperature or high temperature), failing to achieve multiple functions such as inhibition and removal, coking prevention and corrosion prevention, desulfurization and combustion promotion. More importantly, there are no reports in the existing technology of systematically integrating the six categories of components "alkaline substances, rare earth oxides, nucleating agents, oxidants, fluxes and dispersants" and utilizing multiple physicochemical coupling mechanisms such as nucleating agents to induce crystallization, fluxes to induce thermal stress cracks, and dispersants to synergistically form a protective film.
[0013] Therefore, developing a coking inhibitor that can simultaneously achieve efficient coking suppression, removal of existing coking, desulfurization and sulfur fixation, combustion enhancement and energy saving, and corrosion protection of heating surfaces, with significant synergistic effects of its components and adaptability to various furnace types, has important industrial application value and economic benefits. Summary of the Invention
[0014] To overcome the shortcomings of existing technologies, this invention provides a coking inhibitor, its preparation method, and its application. The technical solution of this invention is as follows: A coking inhibitor is composed of the following components: alkaline substances, rare earth oxides, nucleating agents, oxidizing agents, fluxing agents, and dispersants. After the coking inhibitor is sprayed into the high-temperature zone of the furnace, the above components produce a synergistic effect through neutralization, catalysis, crystallization, oxidation, fluxing, pore formation, and corrosion prevention, thereby achieving the functions of inhibiting coking, removing existing coking, desulfurization and sulfur fixation, combustion promotion and energy saving, and corrosion protection.
[0015] The components, by mass parts, are as follows: 30-55 parts of alkaline substance, 5-20 parts of rare earth oxide, 1-8 parts of nucleating agent, 10-30 parts of oxidizing agent, 3-15 parts of flux, and 5-15 parts of dispersant; the alkaline substance is selected from one or more of sodium carbonate, sodium hydroxide, calcium hydroxide, and zinc oxide in any proportion; the rare earth oxide is selected from one or more of cerium oxide, neodymium oxide, and lanthanum oxide in any proportion; the nucleating agent is selected from one or more of zinc powder, zinc oxide, and titanium dioxide in any proportion; the oxidizing agent is selected from one or more of sodium nitrate, sodium nitrite, and potassium nitrate in any proportion; the flux is selected from one or more of borax, sodium chloride, potassium chloride, and calcium fluoride in any proportion; and the dispersant is selected from one or more of silica, diatomaceous earth, and kaolin in any proportion.
[0016] The rare earth oxide is a complex of cerium oxide and neodymium oxide, with a mass ratio of 1:0.3 to 1:1.
[0017] The nucleating agent is zinc powder with an average particle size of 1 to 30 micrometers.
[0018] The coking inhibitor comprises the following components in parts by weight: 40 parts sodium carbonate, 8 parts cerium oxide, 4 parts neodymium oxide, 3 parts zinc powder, 20 parts sodium nitrate, 10 parts borax, and 15 parts silica; the average particle size of the coking inhibitor is 10-50 micrometers, and the moisture content is ≤0.5%.
[0019] The coking inhibitor is applicable to industrial furnaces and kilns, including side-blown furnaces, smelting furnaces, converters, fluidized bed furnaces, rotary kilns, incinerators, coal-fired boilers, biomass boilers, cement kilns, or non-ferrous metal smelting furnaces.
[0020] The method for preparing the coking inhibitor includes the following steps: S1. Weigh out the alkaline substance, rare earth oxide, nucleating agent, oxidizing agent, flux, and dispersant according to the specified ratio; S2. The weighed rare earth oxides are mixed with flux and then pre-ground to obtain a premixed powder. S3. The premixed powder is mixed together with the alkaline substance, nucleating agent, oxidizing agent and dispersant in a high-speed mixer; S4. Sift the powder mixed in step S3. S5. Vacuum dry the powder after sieving in step S4. The vacuum drying temperature is 45-65℃ and the time is 1.5-3 hours. S6. The dried powder is subjected to air jet milling to obtain a coking inhibitor with an average particle size of 10-50 micrometers.
[0021] The application method of the coking inhibitor employs a multi-point distributed injection system, in which the coking inhibitor is injected into the high-temperature zone of the furnace via compressed air at a pressure of 0.3–0.8 MPa. The addition amount is 0.03%–0.6% of the fuel mass, and the addition frequency is once every 2–6 hours. The coking inhibitor undergoes the following reaction or action steps sequentially or simultaneously within the furnace: (a) Neutralization step: Alkaline substances react with sulfuric acid and sulfur trioxide in flue gas to form sulfates, which reduces the adhesion of ash residue; (b) Catalytic step: Rare earth oxides catalyze the oxidation of sulfur dioxide to sulfur trioxide and promote the oxidation and combustion of fuel; (c) Crystallization step: The nucleating agent induces the formation of crystal nuclei in the molten ash, triggering the devitrification of the glass and generating microcracks; (d) Oxidation step: The oxidant decomposes at temperatures above 750°C, releasing nascent oxygen, which reacts with carbon and sulfides, generating localized air blast impacts; (e) Flushing step: The flux forms a low-melting-point glass phase, which penetrates into the coking pores and induces crack propagation due to the difference in thermal expansion coefficients; (f) Pore formation step: After the reaction in steps (a) to (e), the porosity of the coking layer increases, making it loose and porous; (g) Anti-corrosion steps: The dispersant and alkaline substances form a protective film on the heated surface to inhibit acid corrosion.
[0022] The advantages of this invention are: 1. For the first time, six functional components, namely alkaline substances, rare earth oxides, nucleating agents, oxidants, fluxes and dispersants, are systematically compounded. Each component works in the high-temperature zone of the furnace through a chain-like synergistic effect of neutralization, catalysis, crystallization, oxidation, fluxing, pore formation and corrosion prevention. At the same time, it achieves five major functions: inhibiting the formation of new coke, removing existing coke, desulfurization and sulfur fixation, combustion promotion and energy saving, and corrosion protection of the heated surface.
[0023] 2. By inducing the devitrification of the ash slag glass through nucleating agents, the low-melting-point glass phase formed by the flux generates a difference in the coefficient of thermal expansion, causing a large number of microcracks to be generated inside the hard coking layer and gradually expand, eventually making the coking layer loose and porous and falling off on its own.
[0024] 3. The alkaline substances neutralize the sulfuric acid and sulfur trioxide in the flue gas to form high-melting-point sulfates, and the rare earth oxides increase the melting temperature of the ash. The dispersant and the alkaline substances work together to form a dense protective film on the heated surface, preventing the ash from adhering at the source.
[0025] 4. Oxidants decompose and release nascent oxygen, enhancing fuel combustion, especially promoting the complete combustion of fine carbon particles and carbides; rare earth oxides catalyze oxidation reactions, increasing the amount of volatiles released.
[0026] 5. Rare earth oxides and alkaline substances synergistically capture SO2 and SO3 in flue gas, converting them into stable sulfates that are fixed in slag or fly ash, thereby reducing air pollution and meeting environmental protection requirements.
[0027] 6. Dispersants (such as silica) react with alkaline substances at high temperatures to form a sodium silicate-based protective film, effectively blocking the corrosion of metals by sulfuric acid and sulfates. The corrosion rate is reduced by more than 90%, and the service life of key components such as water-cooled walls and superheaters is extended by more than 2 times.
[0028] 7. The preparation method involves steps such as pre-grinding, high-speed mixing, sieving, vacuum drying, and air jet milling. The process is mature, simple to operate, and has excellent flowability and dispersibility, making it easy to store and use.
[0029] 8. This invention can not only reduce fuel consumption and the labor intensity of decoking, but also reduce equipment corrosion and maintenance costs, extend maintenance cycles, and reduce flue gas pollutant emissions. It has outstanding comprehensive economic benefits and is of great significance for promoting energy conservation, emission reduction and clean production. Detailed Implementation
[0030] The present invention will be further described below with reference to specific embodiments, and the advantages and features of the present invention will become clearer as a result. However, these embodiments are merely exemplary and do not constitute any limitation on the scope of the present invention. Those skilled in the art should understand that modifications or substitutions can be made to the details and form of the technical solutions of the present invention without departing from the spirit and scope of the present invention, but all such modifications and substitutions fall within the protection scope of the present invention.
[0031] This invention relates to a coking inhibitor, its preparation method, and its application. The coking inhibitor is composed of the following components: an alkaline substance, rare earth oxides, a nucleating agent, an oxidizing agent, a fluxing agent, and a dispersant. After the coking inhibitor is injected into the high-temperature zone of a furnace, the above components produce a synergistic effect through neutralization, catalysis, crystallization, oxidation, fluxing, pore formation, and corrosion prevention, thereby achieving the functions of inhibiting coking, removing existing coking, desulfurization and sulfur fixation, combustion promotion and energy saving, and corrosion protection.
[0032] Example 1: The following components were weighed in parts by weight: 40 parts sodium carbonate, 8 parts cerium oxide, 4 parts neodymium oxide (total rare earth oxides 12 parts, cerium oxide to neodymium oxide mass ratio 2:1), 3 parts zinc powder (average particle size 20 micrometers), 20 parts sodium nitrate, 10 parts borax, and 15 parts silica. Cerium oxide, neodymium oxide, and borax were mixed and pre-ground to obtain a premixed powder. The premixed powder was then added to a high-speed mixer along with sodium carbonate, zinc powder, sodium nitrate, and silica and mixed evenly. After sieving, the mixture was vacuum dried at 50°C for 2 hours. Finally, it was pulverized by air jet milling to obtain a coking inhibitor with an average particle size of 10–50 micrometers and a moisture content ≤0.5%.
[0033] Example 2: The following components were weighed in parts by weight: 15 parts sodium carbonate, 15 parts sodium hydroxide (total alkaline substances 30 parts), 13.3 parts cerium oxide, 6.7 parts neodymium oxide (total rare earth oxides 20 parts, cerium oxide to neodymium oxide mass ratio 2:1), 8 parts zinc powder, 15 parts sodium nitrate, 10 parts sodium nitrite (total oxidant 25 parts), 6 parts borax, 6 parts sodium chloride (total flux 12 parts), 2.5 parts silica, and 2.5 parts diatomaceous earth (total dispersant 5 parts). The preparation steps were the same as in Example 1, resulting in a coking inhibitor.
[0034] Example 3: The following components were weighed in parts by weight: 41.25 parts calcium hydroxide, 13.75 parts zinc oxide (total alkaline substances 55 parts), 2.5 parts cerium oxide, 2.5 parts lanthanum oxide (total rare earth oxides 5 parts), 1 part zinc oxide (as a nucleating agent), 10 parts potassium nitrate, 3 parts calcium fluoride, and 15 parts kaolin. The preparation steps were the same as in Example 1, resulting in a coking inhibitor.
[0035] Example 4: The following components were weighed in parts by weight: 45 parts sodium carbonate, 10 parts cerium oxide, 5 parts titanium dioxide, 18 parts sodium nitrite, 8 parts borax, and 10 parts silica. The preparation steps were the same as in Example 1, resulting in a coking inhibitor.
[0036] Example 5: The following components were weighed in parts by weight: 40 parts sodium carbonate, 10 parts zinc oxide (total alkaline substances 50 parts), 4 parts cerium oxide, 4 parts neodymium oxide (total rare earth oxides 8 parts), 6 parts zinc oxide (average particle size 15 micrometers, used as a nucleating agent), 22 parts sodium nitrate, 7 parts borax, and 12 parts silica. The preparation steps were the same as in Example 1, resulting in a coking inhibitor.
[0037] II. Control Group Setup Comparative Example 1: Except for replacing cerium oxide and neodymium oxide in Example 1 with an equal amount of sodium carbonate (i.e., increasing the total amount of sodium carbonate to 52 parts), the other components and amounts are exactly the same as in Example 1, and the preparation method is the same.
[0038] Comparative Example 2: Except for replacing the zinc powder in Example 1 with an equal amount of sodium carbonate (i.e., increasing the total amount of sodium carbonate to 43 parts), the other components and amounts were exactly the same as in Example 1, and the preparation method was the same.
[0039] Comparative Example 3: Except for replacing the borax in Example 1 with an equal amount of sodium carbonate (i.e., increasing the total amount of sodium carbonate to 50 parts), the other components and amounts are exactly the same as in Example 1, and the preparation method is the same.
[0040] Comparative Example 4: Except for replacing 8 parts of cerium oxide and 4 parts of neodymium oxide in Example 1 with 12 parts of lanthanum oxide (single rare earth), the other components and amounts are exactly the same as in Example 1, and the preparation method is the same.
[0041] Comparative Example 5 (nucleating agent is quartz powder): Except for replacing 3 parts of zinc powder in Example 1 with 3 parts of quartz powder (average particle size 20 micrometers), the other components and amounts are exactly the same as in Example 1, and the preparation method is the same.
[0042] Comparative Example 6: A commercially available coking inhibitor was selected, whose main components are a simple mixture of sodium carbonate and sodium nitrate, and which does not contain rare earth oxides, nucleating agents, fluxes and dispersants.
[0043] III. Experimental Conditions and Test Methods The experiment was conducted on a side-blown copper smelting furnace, with a furnace temperature range of 1100–1300℃. The coking inhibitors in all examples and comparative examples employed a multi-point distributed injection system, injecting compressed air into the high-temperature zone of the furnace at a uniform injection pressure of 0.5 MPa. The addition amount was 0.2% of the fuel mass, and the addition frequency was once every 4 hours. After 30 days of continuous operation, the following indicators were tested: Coking inhibition rate (%): Calculated by comparing the coking thickness of the heated surface in the untreated area and the treated area. The formula is (coking thickness in the untreated area - coking thickness in the treated area) / coking thickness in the untreated area × 100%.
[0044] Self-stripping time (hours): The time required from the first application of the chemical until large-area cracks are observed in the coking layer and it begins to peel off on its own.
[0045] Thermal efficiency improvement (%): The difference in boiler thermal efficiency before and after chemical addition.
[0046] SO2 emission reduction (%): The percentage decrease in SO2 concentration in flue gas before and after dosing.
[0047] Corrosion rate (mm / year): determined by the weight loss method of water-cooled wall tube specimens and converted into corrosion thickness per year.
[0048] IV. Comparison Table of Experimental Results Example 1 92 72 8.2 65 0.05 Example 2 88 80 7.5 60 0.06 Example 3 85 96 6.8 52 0.08 Example 4 70 120 5.1 40 0.12 Example 5 75 108 5.8 45 0.10 Comparative Example 1 32 >240 1.5 12 0.42 Comparative Example 2 48 No self-peeling 2.2 18 0.35 Comparative Example 3 55 168 3.1 25 0.28 Comparative Example 4 58 168 3.8 30 0.20 Comparative Example 5 52 192 2.9 22 0.30 Comparative Example 6 45 No self-peeling 2.8 20 0.30 V. Analysis of Experimental Results (1) As can be seen from the comparison between Example 1 and Comparative Examples 1, 2, and 3, when rare earth oxides, nucleating agents, or fluxes are lacking, the coking inhibition rate drops sharply from 92% in Example 1 to 32%, 48%, and 55%, respectively, and the self-peeling time is significantly prolonged or even disappears completely (comparative Example 2 has no self-peeling). This fully demonstrates that the six functional components selected in this invention are indispensable. They achieve excellent comprehensive effects through a chain-like synergistic effect of neutralization, catalysis, crystallization, oxidation, fluxing, pore formation, and corrosion prevention. The absence of any component will lead to a significant deterioration in performance.
[0049] (2) Regarding the non-obviousness of component selection. Example 1 uses a combination of cerium oxide and neodymium oxide, and its coking inhibition rate (92%) and self-exfoliation time (72 hours) are both superior to Example 4 (cerium oxide alone, inhibition rate 70%, self-exfoliation time 120 hours) and Comparative Example 4 (lanthanum oxide alone, inhibition rate 58%, self-exfoliation time 168 hours). Example 1 uses zinc powder as a nucleating agent, and its effect (inhibition rate 92%, self-exfoliation time 72 hours) is significantly superior to Example 5 (zinc oxide, inhibition rate 75%, self-exfoliation time 108 hours) and Comparative Example 5 (quartz powder, inhibition rate 52%, self-exfoliation time 192 hours). These data demonstrate that the specific combination of rare earth oxides and the specific materials selected for the nucleating agent in this invention are not arbitrary or conventional, but rather carefully selected specific technical solutions that produce unexpected technical effects.
[0050] (3) Originality regarding the self-peeling characteristic. Examples 1 to 5 all showed the phenomenon of self-peeling of the coking layer (self-peeling time between 72 and 120 hours), while Comparative Example 2 (without nucleating agent), Comparative Example 6 (commercially available product), and most other comparative examples did not observe self-peeling or had extremely long self-peeling times (>240 hours). This indicates that the mechanism of this invention, which induces devitrification of the ash glass body through a nucleating agent, and combines with a flux to form a low-melting-point glass phase, resulting in a difference in the coefficient of thermal expansion, thereby generating a large number of microcracks within the hard coking layer and promoting its looseness, porosity, and self-peeling, is unique and effective, and is not possessed by existing technologies.
[0051] (4) Regarding the rationality of the dosage range. Although the effects of Example 2 (high rare earth, high nucleating agent boundary) and Example 3 (low rare earth, low nucleating agent boundary) are slightly lower than those of Example 1 with the optimal ratio, their coking inhibition rates still reach 88% and 85%, and their self-peeling times are 80 hours and 96 hours, respectively, which are far superior to all comparative examples. This proves that the dosage range of each component defined in claim 2 (30-55 parts of alkaline substance, 5-20 parts of rare earth oxide, 1-8 parts of nucleating agent, etc.) can still maintain significant technical advantages.
[0052] (5) Regarding corrosion prevention and environmental protection effects. The corrosion rate of Example 1 was only 0.05 mm / year, while the corrosion rates of all comparative examples were above 0.20 mm / year, with Comparative Example 1 even reaching 0.42 mm / year. This is due to the reaction of the dispersant (silica) and alkaline substances at high temperatures to form a sodium silicate protective film, which effectively blocks the corrosion of metals by sulfuric acid and sulfates. At the same time, the SO2 reduction in Example 1 reached 65%, far exceeding the 12% of Comparative Example 1 and the 20% of Comparative Example 6, proving that the sulfur fixation mechanism of rare earth oxides and alkaline substances synergistically capturing SO2 and SO3 in flue gas and converting them into stable sulfates fixed in the slag is highly efficient.
[0053] This agent uses Na2CO3, NaOH, Ca(OH)2, ZnO, Ce2O3, Na2O3, etc. for desulfurization, and the chemical reactions are as follows: Na2CO3+SO2←→ Na2SO3+CO↑ (1); 2NaOH+SO2←→ Na2SO3+H2O (2); Na2SO3+SO2+H2O←→2NaHSO3 (3); Equation (1) is the absorption initiation reaction equation; Equation (2) is the main reaction equation: P The H value is 9. When the alkalinity decreases to neutral or even acidic with 5<PH<9, the reaction proceeds according to Equation (3); Regeneration reaction: 2NaHSO3+Ca(OH)2←→ Na2SO3+CaSO3↓+2H2O; Na2SO3+Ca(OH)2←→2NaOH+CaSO3↓; The reaction product easily adheres to slag and dust to fix sulfur in the slag and dust, and deposits in the dust remover, thereby achieving the purpose of sulfur fixation.
[0054] When the rare earth high-efficiency coke remover is fed into the high-temperature furnace chamber, after high-temperature combustion, it interacts with the scale and coke on the metal surface physically and chemically, so that the highly corrosive sulfate, sulfite and oxide slag deposits change from weakly acidic to weakly alkaline, quickly loosen the coke slag and prevent and reduce new coke slag, so as to achieve normal combustion of boiler equipment, improve thermal efficiency, save energy consumption and extend the service life of the equipment.
[0055] When the coke remover is put into the furnace to participate in combustion, it decomposes step by step to generate a variety of strong oxidants and catalysts, and at the same time releases oxygen with heat, which plays a strong combustion-supporting role and promotes the removal of carbon and carbides in the flue gas. In addition, it can also produce a chemical effect with the smoke scale on the heating surface, so that the carbon and carbides in the smoke scale turn into carbon oxides and carbon dioxide and volatilize, reducing the content of carbon and carbides in the flue gas, achieving the purposes of coke removal, dust removal, combustion supporting and desulfurization, thereby improving the efficiency of the boiler, reducing boiler energy consumption, lowering the Ringelmann blackness, reducing air pollution and being beneficial to environmental health.
[0056] Function of the coking inhibitor: This agent effectively removes ash and coke buildup on the heated surfaces of the furnace, maintaining the original high-efficiency heat transfer properties of the equipment and improving the furnace's thermal efficiency. It also eliminates corrosion caused by temperature differences between the coke-covered surface and exposed areas, thus extending the equipment's lifespan. The agent is added automatically and synchronously to the raw material conveying equipment, or via specialized equipment. As fuel enters the high-temperature combustion zone of the furnace, the atomized agent settles on the heated surfaces and reacts chemically with the slag and scale, particularly in the crevices and grooves. It neutralizes acidic fuel components, burns off residual carbon, and forms a low-point double salt eutectic, which liquefies, causing expansion and contraction that loosens the slag and coke layer. The intense flame wave generated by the agent washes over and vibrates the slag and scale layer. The oxidizer decomposes at temperatures above 750℃, generating alkaline substances such as Na₂O, NaNO₂, and NaOH. These alkaline components settle on the ash deposits, reacting with sulfur trioxide diffused to the deposit surface and neutralizing the sticky matrix in the deposit layer. For example: 2NaBO2 + Na2S2O7 → 2Na2SO4 + B2O2; Na₂O + Na₂S₂O₇ → 2Na₂SO₄; Na2CO3+Na2S2O7→2Na2SO4+CO2; The reaction results in the formation of Na₂SO₄, which has a high melting point, eliminating the presence of a sticky matrix. However, Na₂SO₄ is also easily pulverized, significantly reducing the adhesion strength of the sediment. The relatively low acidity of Na₂SO₄ increases the pH of the sediment. This demonstrates the dual effect of the alkaline components: inhibiting fouling formation and reducing fouling intensity. The acidic substance in the sediment of the low-temperature heated surface is mainly H₂SO₄, which is the primary factor causing low-temperature sticky ash fouling. The alkaline substances in the coking inhibitor and many intermediate products formed in the furnace can neutralize H₂SO₄ to form sulfates, thus decreasing the adhesion strength of the sediment and increasing the pH. Simultaneously, the neutralization reaction of alkaline components with SO₃ in the flue gas inhibits the formation of H₂SO₄, thereby preventing ash accumulation.
[0057] Its effects on the oxidation of silicon, iron, and aluminum, and on sulfates: Sodium components in coking inhibitors are strong fluxes. Small amounts of sodium significantly reduce the viscosity of the deposit, and the amounts of iron, aluminum, and silicon oxides and sulfates are also reduced. This is due to the volatilization of low-boiling-point chlorides. After the coking inhibitor falls onto the heated surface, it can react with sulfates to produce sodium sulfate and chloride products, all of which are highly prone to sublimation (AlCl3, FeCl3, SiCl4), thus reducing the sample recovery rate. Due to the uneven distribution of various components and inhibitors in the deposit layer, the physical properties of the deposit are altered. The formation of low-boiling-point chlorides creates new pores, making it easy for cracks to form in the deposit layer when the heat load changes, making the deposit layer loose and easy to detach. Some active substances in the coking inhibitor are combustible or can support combustion. When added to the furnace, they can undergo a violent redox reaction. This reaction is very intense and has a blast effect. The generated Na2S reacts with oxygen. Therefore, as long as there is sufficient nitrate and carbon, a small amount of sulfur can sustain the reaction. Zinc powder acts as a nucleating agent, which on the one hand causes molten or semi-molten ash particles to crystallize rapidly when they reach the heated surface, and on the other hand causes the silica glass body of the deposited layer to devitrify, thereby changing its coefficient of thermal expansion and making the coke slag deposited layer more prone to cracking and falling off.
[0058] In summary, the coking inhibitor of the present invention, under the synergistic effect of its components, has achieved unexpected technical effects in coking inhibition, self-stripping, thermal efficiency improvement, desulfurization and corrosion prevention. Moreover, the specific components and their dosage ranges are non-obvious and significantly superior to the prior art.
[0059] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A coking inhibitor, characterized in that, It is composed of the following components: alkaline substances, rare earth oxides, nucleating agents, oxidizing agents, fluxing agents and dispersants; after the coking inhibitor is injected into the high-temperature zone of the furnace, the above components produce a synergistic effect through neutralization, catalysis, crystallization, oxidation, fluxing, pore formation and corrosion prevention, so as to achieve coking inhibition, removal of existing coking, desulfurization and sulfur fixation, combustion promotion and energy saving and corrosion protection.
2. The coking inhibitor according to claim 1, characterized in that, The components, by mass parts, are as follows: 30-55 parts of alkaline substance, 5-20 parts of rare earth oxide, 1-8 parts of nucleating agent, 10-30 parts of oxidizing agent, 3-15 parts of flux, and 5-15 parts of dispersant; the alkaline substance is selected from one or more of sodium carbonate, sodium hydroxide, calcium hydroxide, and zinc oxide in any proportion; the rare earth oxide is selected from one or more of cerium oxide, neodymium oxide, and lanthanum oxide in any proportion; the nucleating agent is selected from one or more of zinc powder, zinc oxide, and titanium dioxide in any proportion; the oxidizing agent is selected from one or more of sodium nitrate, sodium nitrite, and potassium nitrate in any proportion; the flux is selected from one or more of borax, sodium chloride, potassium chloride, and calcium fluoride in any proportion; and the dispersant is selected from one or more of silica, diatomaceous earth, and kaolin in any proportion.
3. The coking inhibitor according to claim 2, characterized in that, The rare earth oxide is a complex of cerium oxide and neodymium oxide, with a mass ratio of 1:0.3 to 1:
1.
4. The coking inhibitor according to claim 2, characterized in that, The nucleating agent is zinc powder with an average particle size of 1 to 30 micrometers.
5. The coking inhibitor according to claim 2, characterized in that, The coking inhibitor comprises the following components in parts by weight: 40 parts sodium carbonate, 8 parts cerium oxide, 4 parts neodymium oxide, 3 parts zinc powder, 20 parts sodium nitrate, 10 parts borax, and 15 parts silica; the average particle size of the coking inhibitor is 10-50 micrometers, and the moisture content is ≤0.5%.
6. The coking inhibitor according to any one of claims 1 to 5, characterized in that, The coking inhibitor is applicable to industrial furnaces and kilns, including side-blown furnaces, smelting furnaces, converters, fluidized bed furnaces, rotary kilns, incinerators, coal-fired boilers, biomass boilers, cement kilns, or non-ferrous metal smelting furnaces.
7. A method for preparing a coking inhibitor as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Weigh out the alkaline substance, rare earth oxide, nucleating agent, oxidizing agent, flux, and dispersant according to the specified ratio; S2. The weighed rare earth oxides are mixed with flux and then pre-ground to obtain a premixed powder. S3. The premixed powder is mixed together with the alkaline substance, nucleating agent, oxidizing agent and dispersant in a high-speed mixer; S4. Sift the powder mixed in step S3. S5. Vacuum dry the powder after sieving in step S4. The vacuum drying temperature is 45-65℃ and the time is 1.5-3 hours. S6. The dried powder is subjected to air jet milling to obtain a coking inhibitor with an average particle size of 10-50 micrometers.
8. A method for applying the coking inhibitor as described in any one of claims 1 to 6, characterized in that, A multi-point distributed injection system is used to inject the coking inhibitor into the high-temperature zone of the furnace using compressed air. The injection pressure is 0.3–0.8 MPa, the addition amount is 0.03%–0.6% of the fuel mass, and the addition frequency is once every 2–6 hours. The coking inhibitor undergoes the following reaction or action steps sequentially or simultaneously in the furnace: (a) Neutralization step: Alkaline substances react with sulfuric acid and sulfur trioxide in flue gas to form sulfates, which reduces the adhesion of ash residue; (b) Catalytic step: Rare earth oxides catalyze the oxidation of sulfur dioxide to sulfur trioxide and promote the oxidation and combustion of fuel; (c) Crystallization step: The nucleating agent induces the formation of crystal nuclei in the molten ash, triggering the devitrification of the glass and generating microcracks; (d) Oxidation step: The oxidant decomposes at temperatures above 750°C, releasing nascent oxygen, which reacts with carbon and sulfides, generating localized air blast impacts; (e) Flushing step: The flux forms a low-melting-point glass phase, which penetrates into the coking pores and induces crack propagation due to the difference in thermal expansion coefficients; (f) Pore formation step: After the reaction in steps (a) to (e), the porosity of the coking layer increases, making it loose and porous; (g) Anti-corrosion steps: The dispersant and alkaline substances form a protective film on the heated surface to inhibit acid corrosion.